PENGARUH KONTEN PESAN VICE INDONESIA SERI "VAGCHECK" DI YOUTUBE TERHADAP SIKAP MENGENAI PERSONAL HYGIENE : (Survei Pada Followers Akun Instagram @viceind) - Wilda Noviani, (2021)
The purpose of the research is to find out how much the message content from the series 'VagCheck' on Vice Indonesia Youtube channel regarding someone attitude to personal hygiene impact people. (survey from @viceind Instagram account). The relevan theory of this research is Teori Integrasi Informasi (Information Integration Theory). This research are using quantitative method. The research method in this study is the survey method. The population of this research are @viceind Instagram account followers with 100 respondent. The technique of analyzing the impact of Variable X on Variable Y uses a simple linear regression test and the coefficient of determination test. The data testing technique is processed using the SPSS (Statistical Product and Service Solution) version 25 program. The results of this research indicate that correlation of Variable X with Variable Y has a very strong relationship. Based on the calculation of the coefficient of determination, the result of the influence of variable X on variable Y is 71.9%, while the rest is caused by other factors not examined in this study. These results are supported by the results of hypothesis testing, namely Ho is rejected and Ha is accepted, which means that the VICE Indonesia message content in the "VagCheck" series on YouTube has an effect on attitudes regarding personal hygiene during menstruation.